Pancreatic cancer expresses adiponectin receptors and is associated with hypoleptinemia and hyperadiponectinemia: a case-control study. - Dalamaga, Maria; Migdalis, Ilias; Fargnoli, Jessica L; Papadavid, Evangelia; Bloom, Erica; Mitsiades, Nicholas; Karmaniolas, Konstantinos; Pelecanos, Nicolaos; Tseleni-Balafouta, Sofia; Dionyssiou-Asteriou, Amalia; Mantzoros, Christos S (Cancer Causes Control, 2009)
Obesity and insulin resistance have been implicated in the etiology of pancreatic cancer (PC). Whether adiponectin and/or leptin, two adipocyte-secreted hormones important in metabolic regulation, are associated with PC pathogenesis and whether adiponectin receptors are expressed in PC remains unknown. In a hospital-based case-control study, we studied 81 cases with incident, histologically confirmed PC and 81 controls matched on gender and age between 2000 and 2007 to investigate the role of adiponectin and leptin adjusting for risk factors linked to PC. In a separate study, we also studied for the first time whether adiponectin receptors 1 and 2 are expressed in PC by studying 16 PC tumor tissue samples which were analyzed using immunohistochemistry. When subjects were divided into control-defined quartiles of adiponectin and leptin, lower leptin but higher adiponectin levels were associated with PC (p = 0.001 and p = 0.05 respectively) before and after controlling for age, gender, BMI, smoking status, alcohol consumption, history of diabetes, and family history of pancreatic cancer. Of the PC tumor tissue samples analyzed, 87.5% had positive or strong positive expression of AdipoR1 and 93.7% had positive or strong positive expression of AdipoR2. Further prospective studies are needed to determine whether the elevated adiponectin and low leptin levels reported in this study reflect compensatory changes during PC progression and thus can be used as markers for PC or whether they are causally implicated in PC.
Keywords: Adiponectin; Aged; Case-Control Studies; Female; Humans; Insulin Resistance; Leptin; Male; Obesity; Pancreatic Neoplasms; Receptors, Adiponectin